Empowering Elderly People at Risk of Stroke Through Health Education, Physical Activity, and Community-Based Technology - Sri Yani; Nanang Nasrulloh; Agus Joko Susanto (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT Stroke is one of the leading causes of disability and death in Indonesia, especially in the pre-elderly and elderly groups with risk factors for hypertension, diabetes, obesity, and a sedentary lifestyle. This community service program aims to increase public awareness, knowledge, and skills in stroke prevention through health education, physical activity, dietary management, and clean, healthy living behaviors (PHBS). Implementation includes socialization, health counseling, physical activity training, healthy eating support, and optimization of Posbindu and Elderly Posts. The activity results showed increased knowledge among cadres and the elderly about stroke risk factors, increased participation in physical activity, changes in healthy eating behaviors, and greater compliance among the elderly with routine health check-ups. The use of simple technologies, such as WhatsApp groups, gymnastics videos, and applications of the Ministry of Health's Posbindu information system, supports the program's sustainability. The elderly have a moderate stroke risk of 62%, which is the highest risk of stroke. Cadre knowledge increased from 57.5 to 84. Systolic and diastolic blood pressure decreased after interval walking training (IWT). Community-based empowerment through educational approaches, physical exercise, and simple technology has been shown to increase the capacity of people at risk of stroke and to improve health and productivity. It is recommended that this community-based empowerment model be integrated into public health programs on an ongoing basis to expand its impact on stroke prevention and productivity. Keywords: Stroke Risk, Elderly, Education, Physical Activity.